2020
DOI: 10.1183/13993003.01965-2019
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of airway obstruction in lymphangioleiomyomatosis

Abstract: Lymphangioleiomyomatosis (LAM) is a rare, cystic lung disease with progressive pulmonary function loss caused by progressively proliferating LAM cells. The degree of airway obstruction has not been well investigated within the pathogenesis of LAM.Using a combination of ex vivo computed tomography (CT), microCT and histology, the site and nature of airway obstruction in LAM explant lungs was compared with matched control lungs (n=5 each). The total number of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Histological observation shows LAM cysts lined with hyperplasic type II pneumocytes, possibly progressing through underlying chronic inflammation and fibrosis [20]. In both IPF and LAM diseases, the lung has prolonged airway losses, especially in distal parts of the lung parenchyma, leading to severe respiratory failure [21].…”
Section: Introductionmentioning
confidence: 99%
“…Histological observation shows LAM cysts lined with hyperplasic type II pneumocytes, possibly progressing through underlying chronic inflammation and fibrosis [20]. In both IPF and LAM diseases, the lung has prolonged airway losses, especially in distal parts of the lung parenchyma, leading to severe respiratory failure [21].…”
Section: Introductionmentioning
confidence: 99%
“…17 The introduction of microcomputed tomography (microCT) has enabled three-dimensional (3D) morphologic assessments of lung tissues that are very difficult to achieve with conventional histologic analysis. 12,13,18,19 In addition, microCT of frozen air-inflated tissue enables quantitative assessment without shrinkage and physical cutting of tissues. 20 Mai et al 16 combined CT, microCT, and histologic assessment, and found that fibrosis and honeycomb cyst formation in IPF extend from the peripheral to the central region of the pulmonary lobules.…”
mentioning
confidence: 99%
“…Given that both radiologic and pathologic studies consistently demonstrate the existence of multiple presentations of fibrotic sarcoidosis with a potential differential involvement of the airways, we aimed to perform an in depth investigation of the role of the airways in lungs of patients with end-stage fibrotic sarcoidosis undergoing lung transplantation using a combination of CT, microCT and histopathology, as utilized previously in other interstitial lung diseases such as idiopathic pulmonary fibrosis (IPF) 9 and lymphangioleiomyomatosis 10 .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Lung processing for ex vivo CT and whole lung microCT Lungs were processed as previously described 9 . Briefly, one of the explant lungs was airinflated at 30 cm H2O and after deflation to 10 cm H2O, lungs were fixed in the fumes of liquid nitrogen at constant airway pressure, preserved at -80°C and scanned with ex vivo CT in frozen condition (Siemens Somatom, 1.0 mm slice thickness, B60F window) as described previously 9,10 . This CT was used to semi-automatically segment the airways using ITK-SNAP 12 .…”
Section: Patient Selectionmentioning
confidence: 99%